2022
DOI: 10.1002/mgg3.2067
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clinical characteristics of 24 mainland Chinese patients with CTNNB1 loss‐of‐function variants

Abstract: Background: Neurodevelopmental disorder with spastic diplegia and visual defects (NEDSDV) is a rare autosomal dominant syndrome, which is caused by the heterozygous germline loss-of-function variants in CTNNB1. Methods:We evaluated the clinical and genetic findings of 24 previously undescribed Chinese patients affected by CTNNB1-related disorders and explored the possible ethnicity-related phenotypic variations.Results: Twenty-one loss-of-function variants were identified within these 24 NEDSDV patients, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…One large autism genetic study 38 identified CTNNB1 as a risk gene for autism. In our study, caregivers reported an autism diagnosis in 34%, which is higher than the previous studies 1,23 . The report of autism is supported by the results from the SCQ, which found that 33% of individuals had a risk of social communication impairment.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…One large autism genetic study 38 identified CTNNB1 as a risk gene for autism. In our study, caregivers reported an autism diagnosis in 34%, which is higher than the previous studies 1,23 . The report of autism is supported by the results from the SCQ, which found that 33% of individuals had a risk of social communication impairment.…”
Section: Discussionsupporting
confidence: 81%
“…However, Kayumi et al 1 reported a higher frequency of microcephaly (79.8%) and lower frequency of dystonia (7.5%) and tethered cord (9.3%) compared to our study. The Yan et al series 23 reported a similar frequency of microcephaly (69.6%) and higher frequency of dystonia (87.5%) compared to our series.…”
Section: Musculoskeletal Systemsupporting
confidence: 80%
See 1 more Smart Citation
“…A summary of recent publications related to the clinical phenotypes of patients with CTNNB1 mutation is presented in Table 1 . Multiple case reports have described the complicated abnormalities caused by different mutations in CTNNB1, including de novo nonsense mutation ( 47 ), haploinsufficiency ( 42 ), small de novo deletions ( 51 ), with behavioral anomalies, anxiety, impaired motor performance, cognitive impairment as major phenotypes.…”
Section: Ctnnb1-related Ndds In Human Studiesmentioning
confidence: 99%
“…Dixon et al [22] rst reported the relationship between CTNNB1 haploid dysfunction and FEVR in 2016, a few cases have been reported, and the majority of patients are of Asian ethnicity [23,24] . In the study of Yan et al [25] , the clinical characteristics and genetic results of 24 patients with CTNNB1 pathogenic variation in the Chinese Mainland were reported. This is currently the largest case series of NEDSDV caused by CTNNB1 mutation in China.…”
Section: Discussionmentioning
confidence: 99%